A new finite element for thick laminates and sandwich structures using a generalized and unified plate theory. (16th June 2016) - Caliri, Mauricio F.; Ferreira, Antonio J. M.; Tita, Volnei
Summary: The contribution of this work is the implementation of a new elastic solution method for thick laminated composites and sandwich structures based on a generalized unified formulation using finite elements. A quadrilateral four‐node element was developed and evaluated using an in‐house finite element program. The C‐1 continuity requirements are fulfilled for the transversal displacement field variable. This method is tagged as Caliri's generalized formulation. The results employing the proposed solution method yielded coherent results with deviations as low as 0.05% for a static simply supported symmetric laminate and 0.5% for the modal analyses of a soft core sandwich structure. Copyright © 2016 John Wiley & Sons, Ltd.